2021
DOI: 10.1111/bjh.17544
|View full text |Cite
|
Sign up to set email alerts
|

Graft‐versus‐host disease risk after chimeric antigen receptor T‐cell therapy: the diametric opposition of T cells

Abstract: Chimeric antigen receptor (CAR) T-cell therapy has brought a paradigm shift in the management of haematological malignancies and has opened novel avenues of investigational therapeutic strategies. Given these encouraging responses, it has become imperative to understand the full spectrum of biology and potential toxicities that can arise from these novel agents, as well as those under investigation. With the increasing use of CAR T-cell therapy for relapse following allogeneic haematopoietic cell transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 81 publications
0
37
0
Order By: Relevance
“…Diarrhea is a typical symptom of GI GVHD, and in severe cases, bloody stools may be present. Although GVHD risk is relatively low with tisagenlecleucel 6 , a higher incidence of GVHD has been reported in patients treated with the new-generation CAR-T products 6,7 . Furthermore, active GVHD at lymphocyte apheresis is a risk factor for worsening pre-existing GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is a typical symptom of GI GVHD, and in severe cases, bloody stools may be present. Although GVHD risk is relatively low with tisagenlecleucel 6 , a higher incidence of GVHD has been reported in patients treated with the new-generation CAR-T products 6,7 . Furthermore, active GVHD at lymphocyte apheresis is a risk factor for worsening pre-existing GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent review found little published evidence to suggest that other CAR T-cell products generated from patients after HSCT can mediate GVHD. 3 Even the incidence of GVHD following donor-derived CAR T-cells is low (0-15%); 4,5 although in this setting patient/donor selection may play a role: haploidentical donor-derived CAR Tcells have been associated with higher incidence of GVHD, up to 66%. 6,7 With globally increasing access to CAR T-cell products, and the potential for broader indications, the incidence of GVHD after CAR T-cell therapy should be carefully documented as a potential additional toxicity in patients who underwent HSCT.…”
Section: Graft-versus-host Disease Induced By Tisagenlecleucel In Patients After Allogeneic Stem Cell Transplantationmentioning
confidence: 99%
“…Moreover, since the generation of autologous CAR-Ts is not always feasible, allogeneic CAR-Ts may be considered as suitable alternatives (30). However, using allogeneic CAR-Ts is also hindered by two limitations (30,31). The first limitation is the incidence of graft-versus-host disease (GvHD) which can be lifethreatening, and the second limitation is that allogeneic CAR-Ts might be rapidly attacked and eradicated by the immune system of the recipients (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…However, using allogeneic CAR-Ts is also hindered by two limitations (30,31). The first limitation is the incidence of graft-versus-host disease (GvHD) which can be lifethreatening, and the second limitation is that allogeneic CAR-Ts might be rapidly attacked and eradicated by the immune system of the recipients (30,31). Both of these hurdles significantly obstruct the tumoricidal activity of allogeneic CAR-Ts; therefore, counterstrategies are highly required for tackling these caveats (30,31).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation